PERBAIKAN BALOK BETON BERTULANG YANG TELAH MENGALAMI BEBAN PUNCAK DENGAN BAJA SIKU - Masdar Helmi (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2009)
Reinforced concrete beam can crack caused of load which is bigger than it’s capacity. It need aneffort to repair the beam, so the crack appearance and beam failure can be prevented. One of theways to repair is by installation of angel steel beam on out side of beam.The aim of research is to analyze flexural behavior of repaired reinforced concrete beam. Thebehavior contents : flexural strength, crack pattern, and displacement. The dimension of beam is120 mm x 185 mm x 1550 mm which was charged until crack and failed. There are 3 types ofangel steel beam : (50 x 50 x 5) mm, (40 x 40 x 4) mm, (30 x 30 x 3), that are installed in 3positions based on the eccentricity angel steel beam : behind of beam, inside of beam on bottomside, and beside of beam. Dynabolt, 6.5 cm of length and 8 mm of diameter, is installed 3 pieces in500 mm of distance. The sample is charged on 2 points at 1/3 of span.The results show up that the installation of angel steel beam can increase the flexural strengthcompared to flexural strength rest in reinforced concrete beam which had failed, even the originalone. The new crack are appear at around of dynabolt placed that descript there is force transferfrom concrete beam to angel steel beam. The displacement is less than original beam that showup the toughness also increase.